National Evaluation of the LEAA Family Violence Demonstration Program in Five Sites in the United States, 1980-1981 - Fagan, Jeffrey ([Verlag nicht ermittelbar], 2008)
This study focused on the actuarial and situational correlates of domestic violence and the variables that differentiate those who batter their partners from those who are "generally" violent. The study defined violence as physical violence and excluded both psychological abuse and verbal threats. Domestic violence was defined as a man battering his spouse or partner, while extradomestic violence referred to the batterer's involvement in violence outside the home, as reported by the victim of the domestic incident. The data are victim reports concerning batterers collected through face-to-face interviews with 270 former clients of Law Enforcement Assistance Administration (LEAA)-funded family violence programs conducted approximately three months following final contact with the program. The data include demographic variables on both the LEAA-funded program client and her partner, variables detailing the partner's domestic and extradomestic violence, and variables on any services received by the client.